The Implementation of Utilizing Government Capital Funds Policy in the Indonesia Logistics Bureau - Khaq, Akhsanul; Akbar, Bahrullah; Effendy, Khasan; Lukman, Sampara (Badan Pemeriksa Keuangan Republik Indonesia, 2023)
This study analyzes the policy implementation of Government Capital Funds (GCF) for the Indonesia Logistics Bureau (Perusahaan Umum Badan Urusan Logistik, Perum BULOG) to support national food security. This study also aims to identify any obstacles and determine the development of an effective policy model for implementing the policy. This study uses qualitative methods, and the primary data was obtained from informants using the snowball technique collected from in-depth interviews. The result of this study is that the implementation of GCF fund utilization could have been more optimal in achieving the set targets due to several obstacles. These obstacles include the incomprehensiveness and inconsistencies in GCF policy planning, the difficulty of undertaking land acquisition and obtaining an environmental license, GCF funds are much less than the total needs that should be met, and the discontinuation of the RASTRA Program for low-income families and poor food security governance. In addition, developing an implementation model for the effective use of GCF funds requires strengthening the authority of national food security management institutions. This study recommends that the government upgrade the status of Indonesia's Logistics Bureau to become a ministry-level institution. The relationship pattern with the National Food Agency must also be strengthened for better food policy governance.